Innovation in Al-Qur'an Memorization Learning through the At-Tiqrar Method to Improve the Quality of Memorization of Students at Islamic Boarding Schools - Moh Didin Suherman; Chusnul Muali (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of the At-Tiqrar method in improving the quality of Qur’an memorization among students at Pondok Pesantren Nurul Qur’an. The background of this research is based on the phenomenon that many students still experience difficulties in maintaining memorization consistency, weak long-term retention, and a lack of systematic learning strategies in traditional tahfidz programs. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving five key respondents, namely the pesantren leader (R1), a tahfidz teacher (R2), a supervisor/musyrif (R3), and two active students (R4 and R5). Data analysis was conducted using data reduction, data display, and conclusion drawing techniques, with source triangulation to ensure validity. The findings reveal that the At-Tiqrar method is effective in improving the quality of memorization, particularly in fluency, accuracy of recitation, and long-term retention. The method works through structured and repetitive learning, which strengthens students’ memory and supports better mastery of Qur’anic verses. In addition, the success of its implementation is strongly influenced by structured learning systems, intensive mentoring from teachers and supervisors, as well as institutional support from the pesantren. However, several challenges were identified, including student boredom, individual differences in memorization ability, and limited time allocation. Despite these challenges, adaptive strategies such as method variation and motivational approaches were applied to maintain learning effectiveness. The study concludes that the At-Tiqrar method is an effective and contextual innovation in tahfidz learning, contributing both theoretically and practically to the development of Qur’anic education in Islamic boarding schools in the modern era.